PENGEMBANGAN SISTEM INFORMASI PELAPORAN PENYAKIT TIDAK MENULAR RAWAT INAP DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG TAHUN 2011 - Setyowati Purwaningsih; Maryani Setyowati; Arif Kurniadi (Dian Nuswantoro Semarang, 2012)
Background. Report Information System of In-Patient Non Transmitted Diseases in Semarang Sultan Agung Islamic Hospital that was computer base, it couldn’t makes informationwhich user want. This is because of the should report form is not same with now report form. So, this matter cause officer has to work twice activity for makes the right report form. The aim of this research is make the suggest design of Report Information System of In-Patient Non Transmitted Diseases in Semarang Sultan Agung Islamic Hospital.Method. The type of the research is descriptive with approach of cross sectional to obtained data at the time of the research is done. The research instrument are observation and interviewwith sistem user. The research instrument consist of patient identity data, in-patient registrasion data, in-patient diagnose data, and exit patient data. Processing data are collecting,classification, tabulation, and report, it is also analising to compare between old system with new system.Result. From the result of the research, the process of Report of In-Patient Non Transmitted Diseases are input patient identity data by officer of TPPRJ, input in-patient registrasion databy officer of TPPRI, input in-patient diagnose data and exit patient data from in-patient medical record document by officer of input data of medical record. From this, officer of report toprint the Report of In-Patient Non Transmitted Diseases, Report of In-Patient Non Tranmitted Diseases per Disease, Report of In-Patient Non Transmitted Diseases per Age, Report ofIn-Patient Non Tranmitted Diseases per Sex, and Report of In-Patient Non Transmitted Diseases per Exit.Conclusion.There are not found the Right Policy and Procedure which specific about manual or system of Report of In-Patient Non Transmitted Diseases. The fault of the now systemcan be repaired with the new system that suggest of researcher. So, the result of information can be easy and accurate.Keywords : Report Information System, In-Patient Non Transmitted Diseases